Ultrasonic-assisted extraction (UAE) of tannins from stem bark of Jatropa Curcas - Wan Anis, Wan Azman (2010)
Jatropha curcas, is gaining lot of importance in medicinal uses. The bark of Jatropha Curcas presents a good source of functional compounds, such as polyphenols. Ultrasound-assisted Extraction is evaluated as a simpler and more effective to conventional extraction for isolation of tannins from Jatropha Curcas stem bark. The purposes of this study are to extract tannins from stem bark of of Jatropha Curcas and also to determine the optimum condition to extract the tannins. The effects of solvent ratio (ethanol:water), temperature, extraction time, and amplitude of sonication were studied. Ethanol was used as solvent in this experiment. Extraction was done by using Ultrasounic-assisted extraction, which potentially enhances extraction of polyphenolics. Purification of tannins using rotary evaporator need to be done in order to obtained pure extract. Total phenolic content can be determined spectrophotometrically using Folin–Ciocalteau method. To obtain the amount of Gallic acid in extract, HPLC was used. In this experiment, the analysis revealed that the optimized conditions were when the particle was 1.0 mm in size, a temperature of 30⁰C, an amplitude of 40%, an extraction time of 30 minutes and 1:0 (v/v) ethanol:water ratio. For the conclusion, extraction of tannins using Ultrasound-assisted Extraction was achieved and the optimum condition to extract tannins from Jatropha Curcas stem bark was obtained.